2022
DOI: 10.1371/journal.pcbi.1010696
|View full text |Cite
|
Sign up to set email alerts
|

Using genetic data to identify transmission risk factors: Statistical assessment and application to tuberculosis transmission

Abstract: Identifying host factors that influence infectious disease transmission is an important step toward developing interventions to reduce disease incidence. Recent advances in methods for reconstructing infectious disease transmission events using pathogen genomic and epidemiological data open the door for investigation of host factors that affect onward transmission. While most transmission reconstruction methods are designed to work with densely sampled outbreaks, these methods are making their way into surveil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Although previous evaluations have shown that TransPhylo has a good performance identifying tuberculosis transmitters, this method still presents some limitations. 30 One of these is that transmitters might not be identified as such if the individuals they transmitted to are unsampled. In our study, we applied two correcting strategies to account for such a potential bias: we limited the multivariable analyses to individuals diagnosed before the last 2 years of the study (before 2016, thus allowing an incubation time of 2 years), and adjusted the regression models by diagnosis date.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous evaluations have shown that TransPhylo has a good performance identifying tuberculosis transmitters, this method still presents some limitations. 30 One of these is that transmitters might not be identified as such if the individuals they transmitted to are unsampled. In our study, we applied two correcting strategies to account for such a potential bias: we limited the multivariable analyses to individuals diagnosed before the last 2 years of the study (before 2016, thus allowing an incubation time of 2 years), and adjusted the regression models by diagnosis date.…”
Section: Discussionmentioning
confidence: 99%
“…The stochasticity of parameterization further discourages over-fitting of the model to the simulated data. Beginning with a single infected individual, rate of transmission of infection to susceptible individuals varied according to two scenarios—1) transmission of an acute infectious respiratory virus (ARI) or 2) transmission of Mycobacterium tuberculosis (TB) among populations of HIV-infected or HIV-uninfected individuals, as described in [ 38 ]. Specific paramaters for each outbreak scenario are described in more depth below.…”
Section: Methodsmentioning
confidence: 99%
“…These groups were further split into static and dynamic transmitting groups. Based on a reported average of 53% percent of infection recipients harboring HIV [ 39 ], infection rate for HIV risk groups A and D were 0.53/2 = 26.5%. Remaining non-HIV-infected risk groups B and E comprised the remaining 47% (equally represented).…”
Section: Methodsmentioning
confidence: 99%
“…For example, identifying the central role of incarceration in community transmission of TB in certain settings [54,55]. The limitation of transmission trees is that it cannot be applied to every transmission cluster as a minimum number of cases and SNPs are needed among others [56]. Thus whole genome sequencing is enabling the transition from a cluster-based molecular epidemiology to an individual-based one.…”
Section: Use Of Whole-genome Sequencing (Wgs)mentioning
confidence: 99%